As práticas e representações femininas no protestantismo de Campina Grande: a igreja evangélica congregacional (1927-1960) - Freitas Júnior, Cleófas Lima Alves de (2010)
The objective of this work is to analyze the historic construction of female congregational practices and representations from 1927 to 1960. Considering the resistence of certain women that subvert ideal traditions in love relationships, in faith, in esthetic, body care and fun. The theoretical references of English social history help us to think about those representations in Thompson (1981) his concept of affective and moral conscience . We got closer to culture history in female culture works and gender relations. Analyzing wrong practices of women in Chartier (1990) with the notions of representation and appropriation of Certeau (2008) like a movement of overruns, cheat, trickery and cunning . undo the others‟ game , own inventions in the church‟s discipline.